A comparative analysis of social vulnerability to household food security of Raya Kobo and Raya Alamata Weredas, Ethiopia - Hidaru, Agezew; Tolossa, Degefa; Tilahun, Temesgen (Frontiers in Sustainable Food Systems, 2023)
The study was conducted in Ethiopia's neighboring weredas, Raya Alamata in Tigray and Raya Kobo in Amhara regional states, to determine the reasons for disparities in household food security in the two districts. The goal was to see if there was a link between social vulnerability and food security among households in the two weredas. It employed both qualitative and quantitative methods using Aloui Zouhaier governance Model. Despite their near proximity, similar work habits, natural resource availability, and land size, the Raya Alamata and Raya Kobo communities have a substantial gap in food security and social vulnerability, with Raya Alamata reporting 84% food insecurity and Raya Kobo reporting 24%. The study examined the degree of social vulnerability and food security of households, with irrigation systems, agricultural input consumption, extension packages, and other support systems being the primary variables connected to disparities in food security between the two weredas. Differences in social vulnerability and food security between the two weredas were mostly attributable to households' lack of access to irrigation systems, agricultural supplies, and extension services, which were exacerbated by Raya Alamata's ostensibly, intended administrative marginalization. The study recommends that basic social infrastructure, such as irrigation infrastructure, extension services, agricultural supplies, roads, standard education, health infrastructure facilities, etc., be provided to households in the area and that the federal government should hold the regional and local government bodies accountable for the failures to ensure the provision of the services that could realize a reduced level of social vulnerability to food insecurity.